Production Planning for Spinach, Kale, and Hydroponic Pakchoi Using Linear Programming - Lilis Imamah Ichdayati; Riefqi Aulia Ramdhani; Titik Inayah; Rizki Adi Puspita Sari; Acep Muhib; Achmad Tjahja Nugraha (Jurnal Penelitian Pendidikan IPA, 2025)
Vegetable consumption has been on the rise in 2024, and projections suggest that by 2030, it will reach 17.48 million tons, equivalent to 62.4 kg per capita per year. This growing demand presents a valuable opportunity for 13,019 individual agricultural businesses engaged in urban farming. One of the key advantages of hydroponic vegetables is their freshness, as they are sold along with the hydroponic installation itself. However, producing hydroponic spinach, kale, and pakchoy comes with challenges, especially for companies looking to optimize production costs. This study aims to identify the best production combination to minimize expenses. Using linear programming analysis through the LINDO application, this study examines decision variables—hydroponic spinach (H1), kale (H2), and pakchoy (H3)—with constraints based on both internal factors (seeds, nutrients, growing media, planting holes, and labor) and external factors (customer demand). The results indicate a 2.14% cost reduction, amounting to Rp. 8,148,745, with an optimal production mix of 2,696 units of hydroponic spinach, 2,101 units of hydroponic kale, and 2,448 units of hydroponic pakchoy. To further improve cost efficiency, PT Sarindah Wicaksana is advised to carefully allocate resources based on optimal demand and implement a well-structured production plan.